PELAKSANAAN PROGRAM SABTU BUDAYA DALAM MENUMBUHKAN MULTIKULTURALISME PADA PESERTA DIDIK (STUDI DI SMK NEGERI 1 LOPOK KABUPATEN SUMBAWA ) - Galu Wati; Yuliatin; Basariah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the cultural saturday program in fostering multiculturalism among students at SMKN 1 Lopok, Sumbawa Regency, and to identify the factors that influence its implementation. A qualitative approach with a phenomenological design was used, with data collected through interviews, observations, and documentation. The informants consisted of the school principal, teachers, and students. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was tested through technique triangulation, source triangulation, and time triangulation. The results showed that the cultural saturday program has significantly contributed to fostering multiculturalism through regular Saturday activities that reflect the cultures of the three major ethnic groups in West Nusa Tenggara: Sasak, Samawa, and Mbojo. These activities include: (1) Gemar Gatra gymnastics integrated with traditional movements and games, accompanied by traditional music instruments; (2) student cultural exhibitions featuring items such as woven bags with Sumbawan patterns, Sasak traditional house miniatures, and Mbojo cultural posters; (3) traditional costume competitions displaying songket fabrics and distinctive ethnic attire like sapuq and lambung (Sasak), lamung pene (Samawa), and rimpu (Mbojo); and (4) the performance of regional songs such as Sabalong Samalewa (Sumbawa), Budaye Sasak (Lombok), and Nangi Dana Tambora (Bima). However, there are factors that influence the implementation of the cultural saturday program at SMKN 1 Lopok, Sumbawa Regency, which are divided into two main categories, namely: 1) Supporting factors, consisting of internal factors (human resources) and external factors (community and parental involvement). 2) Inhibiting factors, consisting of internal factors (limited facilities and infrastructure) and external factors (social environment and local cultural conditions).